PENGARUH MODEL RECIPROCAL TEACHING TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA KELAS VII SMP NEGERI 6 PURWOKERTO - Artiah Artiah; Reni Untarti (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2017)
This research aimed to determine whether the reciprocal teaching model affects the ability of students’ mathematical representation or not. The research design used was post test only control design. Sampling used cluster random sampling by taking two classes namely, class VII B as the experimental class and class VII A as the control class. The location of the research was SMP Negeri 6 Purwokerto. As for obtaining data used post test the ability of mathematical representation, the post test question in the form of description. Post test result of mathematical representation ability showed experiment calss average was 65.23, while control class equal to 59.31. Also it obtained the score of hypothesis testing using independent sample t-test as follows, Sig. = 0.051/2 = 0.0255 with 0.05 which means Sig < 0.05 or 0 H is rejected. It can be concluded that the reciprocal teaching model affecs the ability of mathematical representation. Keyword: Mathematical Representation Ability, Reciprocal Teaching.